Learning English through Task-based Methodology - Khar, Meenakshi (THE PRIMARY TEACHER, 2006)
The principal aim of English teaching in today’s world has changed fundamentally. English is to be taught as means of communication, to be used in its spoken form in all situations of contemporary life. The visible impact of the presence of English is that today it is being demanded at the very intial stage ofschooling. The mushrooming of private English medium schools and the early introduction of English in the state school systems is an example of this. Languages are learned implicitly by comprehending and communicating messages, either through listening or reading for meaning. Input rich communicational environments are a prerequisite for language learning. The “burden of languages” is the burden of incomprehension. This happens when language is taught for its own sake as a set of forms and rules, and not introduced and familiarised as the carrier of coherent textual meaning. A number of researchers have stressed that language is acquired when attention is focused not on language form, but on the meaning of messages. The learner should receive meaningful language input that is appropriate to her or his age; knowledge of language and readiness for language skills. The aim at the initial levels i.e. first or first two years of English is to build familiarity with the language through primarily spoken or spoken-and-written input so that the child builds up a working knowledge of the language.